Hari Ahad dalam Pandangan Islam dan Kristen - Setiawan, Hari (ANWARUL, 2023)
Sunday for Christians and Sunday for Muslims have their own understanding, meaning and history for Islam and Christianity. This is what attracts the writer so that the writer wants to conduct a more in-depth study and analysis through various literature related to Sunday in the view of Islam and Christianity. Based on the background of the problem above, the writer tries to conduct a research using a scientific method. so that it is clearly known "Sunday in the View of Islam and Christianity. The purpose of this study was to find out the views of Islam and Christianity on Sundays, and to find out the similarities and differences of Sundays in the views of Islam and Christianity. This research method is a library research method, namely studying books or references from various literature. The findings as well as the results of this research are that Muslims and Christians have different views about Sunday, wherein Islam in Islam does not recognize Sunday but calls it Sunday where Islam calls it Sunday which means one or one, while Christians call it Sunday. holy day, great day and has various other features regarding Sunday. Muslims and Christians have differences and similarities regarding Sunday (Sunday) where the difference relates to the meaning and meaning of Sunday while the similarity is that Sunday (Sunday) is the same Sama stated that it was the first day of the creation of the universe and from an international agreement that Sunday is an international holiday for all activities, even though Islam has Friday as a special day and a holiday as well as a day of hospitality.